Experimental Investigation On Piezoelectric And Electromagnetic Hybrid Micro-Power Generator - Noraini, Mat Ali; Kok, Swee Leong; Ain Atiqa, Mustapha (Asian Research Publishing Network (ARPN), 2016)
Piezoelectric micro-generator (MG) is popular due to its high output power density compared to other means of energy harvesting mechanism; however the current generated is relatively low. In the other hand electromagnetic MG is capable to generate higher output current per unit of electrical output power. By combining both of these MGs, they would complement each other in improving the total efficiency of the energy harvesting system. It is verified from the experiment that the hybrid system reduce the capacitor charging time compared to individual system.